A London Sumting Dis... - Gilroy, Paul (2003)
Texto transcripto de la conferencia London: Postcolonial City por Paul Gilroy en Architectural Association, marzo 1999
Keywords: URBANISMO; CRITICA; HISTORIA; INGLATERRA; LONDRES; SIGLO XX; SOCIEDAD; ETNOLOGIA; INMIGRACION; CONFERENCIAS